Het Rozeknopje. (Turnhout : Vrouwencafé, 1997)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijksRedactie : Turnhoutseweg 45, 2340 Beerse ; vanaf 01(1997) 3 : p/a Kongostraat 76, 2300 Turnhout
Nederlands
Periodiek